Clinical Efficacy of a Novel Therapeutic Principle, Anakoinosis - Daniel Heudobler; Michael Rechenmacher; Florian Lüke; Martin Vogelhuber; Sebastian Klobuch; Simone Thomas; Tobias Pukrop; Christina Hackl; Wolfgang Herr; Lina Ghibelli; Christopher Gerner; Albrecht Reichle (Frontiers Media S.A., 2018)
Classic tumor therapy, consisting of cytotoxic agents and/or targeted therapy, has not overcome therapeutic limitations like poor risk genetic parameters, genetic heterogeneity at different metastatic sites or the problem of undruggable targets. Here we summarize data and trials principally following a completely different treatment concept tackling systems biologic processes: the principle of communicative reprogramming of tumor tissues, i.e., anakoinosis(ancient greek for communication), aims at establishing novel communicative behavior of tumor tissue, the hosting organ and organism via re-modeling gene expression, thus recovering differentiation, and apoptosis competence leading to cancer control - in contrast to an immediate, "poisoning" with maximal tolerable doses of targeted or cytotoxic therapies. Therefore, we introduce the term "Master modulators" for drugs or drug combinations promoting evolutionary processes or regulating homeostatic pathways. These "master modulators" comprise a broad diversity of drugs, characterized by the capacity for reprogramming tumor tissues, i.e., transcriptional modulators, metronomic low-dose chemotherapy, epigenetically modifying agents, protein binding pro-anakoinotic drugs, such as COX-2 inhibitors, IMiDs etc., or for example differentiation inducing therapies. Data on 97 anakoinosis inducing schedules indicate a favorable toxicity profile: The combined administration of master modulators, frequently (with poor or no monoactivity) may even induce continuous complete remission in refractory metastatic neoplasia, irrespectively of the tumor type. That means recessive components of the tumor, successively developing during tumor ontogenesis, are accessible by regulatory active drug combinations in a therapeutically meaningful way. Drug selection is now dependent on situative systems characteristics, to less extent histology dependent. To sum up, anakoinosis represents a new substantive therapy principle besides novel targeted therapies.